Investigating a Quadratic Bezier Curve Due to N-C-W and N-Bishop Frames - Kusak Samancı, Hatice; İncesu, Muhsin (My University, 2020)
The purpose of our paper is to investigate N-Bishop frame of the quadratic Bezier curve which is one of the effective methods for computer-aided geometric design (CAGD). Then the N-Bishop curvatures and derivative formulas for quadratics Bezier curve are calculated and give some numeric examples.